(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
“Health and Disease” are very often considered to be the polar word. Medical anthropology emerged basically with the study of health care system prevalent in the societies. In different parts of the world man devise numerous mechanisms for ensuring health and eliminating disease. Concept of health and illness are not universal in natural and content. These vary from society to society; culture to culture. Different studies conducted among the different groups of people in regards reveal that every human community has its emic views with regards to health, disease and disease-etiology. This fact is relatively more conspicuous in the traditional societies, especially in the simpler ones. The present study conducted among the Mishings of Bamun Doloni village of Lakhimpur district, Assam. In the study an attempt has been made to understand the socio-cultural dimension of the health as well as the traditional health care practices of the people. Various methods and techniques were applied depending on the nature of enquiry.